2007
DOI: 10.1097/scs.0b013e31812f7584
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Craniofacial Bone Growth Disturbances

Abstract: Multimodality treatment, including radiotherapy, chemotherapy, and surgery, is required for the management of head and neck cancer in pediatric patients. Despite the modern advances in radiation dosing and targeting techniques, the radiation damage to the growing craniofacial skeleton in children remains a significant clinical problem. The first part of this review summarizes the clinical effects of radiotherapy on craniofacial bone growth in children. Experimental evidence on therapeutic radiation effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 48 publications
1
19
0
2
Order By: Relevance
“…Although accumulated evidence emphasizes the detrimental effects of therapeutic irradiation on bone (1,(12)(13)(14)(15), there are reports showing positive effects on osteoblastic differentiation and bone-specific gene expression (5,8,16). In this study, we demonstrated that X-ray radiation at relatively low doses accelerated mineralization of calvarial primary osteoblasts with an attendant increase in ALP activity.…”
Section: Discussionmentioning
confidence: 55%
“…Although accumulated evidence emphasizes the detrimental effects of therapeutic irradiation on bone (1,(12)(13)(14)(15), there are reports showing positive effects on osteoblastic differentiation and bone-specific gene expression (5,8,16). In this study, we demonstrated that X-ray radiation at relatively low doses accelerated mineralization of calvarial primary osteoblasts with an attendant increase in ALP activity.…”
Section: Discussionmentioning
confidence: 55%
“…Craniofacial abnormalities, which may impact the oral cavity, occur in 35 to 90 % of children who receive high-dose radiotherapy to the head and neck [20, 37, 4850]. Such abnormalities are often associated with oral cavity sequelae such as dental anomalies, xerostomia, and trismus [50].…”
Section: Resultsmentioning
confidence: 99%
“…Such abnormalities are often associated with oral cavity sequelae such as dental anomalies, xerostomia, and trismus [50]. Cosmetic deformities and the requirement for multiple surgical reconstructions can deeply impact quality of life in long-term survivors [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of leukemia was indicated to be higher in children under 5 years of age who underwent CT scan for the head region (14). There are also long-term side effects of radiation in the treatment of pediatric head-neck cancers, such as growth retardation of maxillofacial bones, severe facial deformities, and skin cancers (15,16).…”
Section: Discussionmentioning
confidence: 99%